PENELITIAN KUANTITATIF DAN KUALITATIF ILMU PERPUSTAKAAN (SEBUAH KOMPARASI) - Mafar, Fiqru (Jurnal Ilmu Budaya, 2011)
Quantitative and qualitative research in library science are debatable. It’s because library science is an interdiscipliner science. This article try to show the differents betwen quantitative and qualitative researchs. By defining and show the example of both research, we get the basic different of quantitative and qualitative research. Quantitative research usually uses number in analyzing data and qualitative does not.